Diosgenin prevents bone loss on retinoic acid-induced osteoporosis in rats. (August 2016) - Zhao, S.; Niu, F.; Xu, C.-Y.; Liu, Y.; Ye, L.; Bi, G.-B.; Chen, L.; Tian, G.; Nie, T.-H.
Abstract Objective To observe the preventive and therapeutic effects of diosgenin on retinoic acid-induced osteoporosis in rats. Methods A total 50 Sprague-Dawley rats were randomly divided into 5 groups: control group, model group (osteoporosis rats), low (10 mg kg−1 ), middle (30 mg kg−1 ), and high-dose diosgenin (90 mg kg−1 )-treated groups. The osteoporosis rats model was induced by retinoic acid. The BMD and physical parameters of femoral including length, wet weight, and dry weight in each group were measured. The hematoxylin–eosin staining was used for bone histomorphology analysis. Besides, the bone calcium (Ca) and phosphorus (P) contents were measured. In order to detect the biochemical index in different treatment groups, the serum tartrate-resistant acid phosphatase (TRAP), alkaline phosphatase (ALP), estradiol, and osteocalcin were compared among different groups. Results The osteoporosis rat model was successfully induced by retinoic acid. Compared with the model group, the lessening of femoral length and weight and the loss of BMD were significantly improved in diosgenin groups. Both contents of Ca and P were much more increased when induced by retinoic acid (p  < 0.05). The estradiol and osteocalcin levels in the middle and high-dose treatment groups were significantly higher than that of the model group, while the ALP and TRAP levels were much lower than the model group (p  < 0.05). Conclusion Diosgenin can prevent the loss of bone in experimental rats. The mechanism may be that it improves the level of estrogenic hormone of estradiol and inhibits the high bone turnover.